Microalgae, sunlight, and starch: low cell concentration is optimal for outdoor production under nutrient stress - A. Six; P. Chambonnière; P. Alvarez; S. Fon-Sing; C. Lancelon-Pin; J.-L. Putaux; J.-F. Sassi; Y. Li-Beisson; G. Fleury (Bioresource Technology, 2026)

Active site-rich MIL-101(Fe) derived P-doped iron sulfide/carbon octahedra for oxygen evolution electrocatalysis - Ying-Jun Jhang Jian; Pin-Yan Lee; Subbiramaniyan Kubendhiran; Lu-Yin Lin; Kevin C.-W. Wu; Kuo-Chuan Ho (Journal of Environmental Chemical Engineering, 2026)

Achieving high specific capacitance via cobalt doping over Nb4C3Tx with boron nitride composite for supercapacitor application - Nikhil Prabhakar; M. Lakshmi Narayanan; Haidee Mana-ay; N. Ponpandian; C. Viswanathan; Pin-Yi Chen (Fuel, 2025)

P30-23 Boosting Early-Stage ADC Toxicity assessment through human in vitro cell models - B. Recolin; C. Rodger; J. Caruana Santiago; S. Randle; R. Foreman; K. Khan; M. Barbara; J. Kwon; R. Lucey; K. Pryde; M.-Y. Lee; S. Liu; et al. (Toxicology Letters, 2025)

Bovine tracheal organoids for studying Mycoplasma bovis respiratory infections - Chintha K. Premachandre; Pin Shie Quah; Bang Manh Tran; Elizabeth Vincan; Georgia Deliyannis; Chinn Yi Wong; Andrés Diaz-Méndez; David C. Jackson; Patrick C. Reading; Glenn F. Browning; Paola K. Vaz; Nadeeka K. Wawegama (Veterinary Microbiology, 2025)

A horizon scan of biological conservation issues for 2025 - William J. Sutherland; Peter N.M. Brotherton; Holly M. Butterworth; Stewart J. Clarke; Tammy E. Davies; Nigel Doar; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jonathan Hughes; et al. (Trends in Ecology & Evolution, 2025)

From raw microalgae to bioplastics: Conversion of Chlorella vulgaris starch granules into thermoplastic starch - A. Six; D. Dauvillée; C. Lancelon-Pin; A. Dimitriades-Lemaire; A. Compadre; C. Dubreuil; P. Alvarez; J.-F. Sassi; Y. Li-Beisson; J.-L. Putaux; N. Le Moigne; G. Fleury (Carbohydrate Polymers, 2024)

Chiral nematic nanocomposites with pitch gradient elaborated by filtration and ultraviolet curing of cellulose nanocrystal suspensions - S. Mandin; L. Metilli; M. Karrouch; C. Lancelon-Pin; J.-L. Putaux; W. Chèvremont; E. Paineau; N. Hengl; B. Jean; F. Pignon (Carbohydrate Polymers, 2024)

Red light induces starch accumulation in Chlorella vulgaris without affecting photosynthesis efficiency, unlike abiotic stress - A. Six; A. Dimitriades-Lemaire; C. Lancelon-Pin; J.-L. Putaux; D. Dauvillée; D. Petroutsos; P. Alvarez Diaz; J.-F. Sassi; Y. Li-Beisson; G. Fleury (Algal Research, 2024)

Evaluating the phytotoxicities of two Irish red seaweeds against common weed species - Onyedika C. Chukwuma; Shiau Pin Tan; Helen Hughes; Peter McLoughlin; Niall O’Toole; Nick McCarthy (Journal of Applied Phycology, 2024)

Geochronological record of Cadomian exterior orogen reworking in bi-modal igneous protoliths of the Cabo Ortegal Allochthon (NW Iberia): the Cambrian onset of the Palaeozoic plate-tectonic cycle - A. Beranoaguirre; B. Ábalos; S. García de Madinabeitia; J-L. Paquette; C. Pin; M.E. Sánchez Lorda; J.F. Santos Zalduegui; P. Puelles; J.I. Gil Ibarguchi (International Geology Review, 2024)

Aquaculture governance: five engagement arenas for sustainability transformation - Stefan Partelow; Furqan Asif; Christophe Béné; Simon Bush; Aisa O Manlosa; Ben Nagel; Achim Schlüter; Vishnumurthy M Chadag; Afrina Choudhury; Steven M Cole; Richard S Cottrell; Stefan Gelcich; et al. (Current Opinion in Environmental Sustainability, 2023)

Unveiling the fates of nitro-transformation products in advanced oxidation process: A DFT-based kinetic model - Pin Wang; Lingjun Bu; Lu Luo; Yangtao Wu; Weiqiu Zhang; Shiqing Zhou; John C. Crittenden (Chemical Engineering Journal, 2023)

The Coorg Block, southern India: Insights from felsic and mafic magmatic suites on Mesoarchean plate tectonics and correlation with supercontinent Ur - Cheng-Xue Yang; M. Santosh; Jarred C. Lloyd; Stijn Glorie; Pin Gao; Bing Yu; Y. Anilkumar; K.S. Anoop; Sung-Won Kim (Gondwana Research, 2023)

Genomic prediction of agronomic and malting quality traits in six-rowed winter barley - G. Charmet; P. A. Pin; M. Schmitt; N. Leroy; B. Claustres; C. Burt; A. Genty (Euphytica, 2023)
While two-rowed barley is usually preferred for malting and beer-making, six-rowed malting barley varieties appeared in Europe around 30 years ago, and several breeders have dedicated improvement programs on this specific germplasm. In this study, we evaluated the feasibility of genomic prediction for yield and malting related traits using 679 breeding lines from two French barley breeders, as well as a set of recently registered varieties. These lines were evaluated in five locations and two harvest years in an unbalanced design. Although the germplasm from the two breeders does show some trend towards differentiation, globally the whole panel did not show a clear-cut genetic structure. Predictive ability of GBLUP was evaluated through random cross-validation within and across breeder sets, and using cross-prediction between breeder sets. Results show moderate to high predictive ability (PA), particularly for malt friability and β-glucan content, for which predictive ability of 0.8 was obtained with training populations as small as 105 registered varieties and across breeding sets. The long range of useful linkage disequilibrium in this particular germplasm allows using as few as 2000 to 5000 markers to obtain high PA. Other prediction methods such as Bayesian LASSO, Bayes Cpi or EGBLUP did not improve predictive ability. These results are very encouraging for implementing genomic prediction of malting quality traits in applied breeding programs.

First Confirmed Record of the Smalltooth Sand Tiger, Odontapis Ferox, in Galicia (NW Spain) - Gonzalo Mucientes; Nair Vilas-Arrondo; Giulia Secci-Petretto; Uxía Vázquez; Xabier Pin; Alfredo López; L. Filipe C. Castro; Elsa Froufe (Thalassas: An International Journal of Marine Sciences, 2023)
The smalltooth sand tiger shark Odontaspis ferox (Risso, 1810) appears to have an extensive and fragmented distribution in tropical and warm-temperate worldwide oceans. One female of O. ferox was caught and released by a small-scale fishery vessel in Ría de Arousa (Northwest of Spain), subsequently stranded still alive on the coast (42°33’18.4"N 8°49’18.3"O) after a few hours. The individual (336 cm total length, weight ~ 300 kg) was identified based on a collection of features including the characteristic dentition, body morphology and by molecular assignment. This is the first confirmed record of O. ferox in Galician waters. This finding complements the knowledge of the geographic distribution and occurrence of this rare and sparse species in the Northeastern Atlantic.

Mouse organoids as an in vitro tool to study the in vivo intestinal response to cytotoxicants - F. Jardi; C. Kelly; C. Teague; H. Fowler-Williams; D. C. Sevin; D. Rodrigues; H. Jo; S. Ferreira; B. Herpers; M. Van Heerden; T. de Kok; C. Pin; et al. (Archives of Toxicology, 2023)

Association between household cleaning product profiles evaluated by the Ménag’Score® index and asthma symptoms among women from the SEPAGES cohort - Pierre Lemire; Emmanuel Chevallier; Sarah Lyon-Caen; Etienne Sévin; Anne Boudier; Emilie Pacheco Da Silva; Christian De Thuin; Rémy Slama; Orianne Dumas; Valérie Siroux; Nicole Le Moual; E. Eyriey; et al. (International Archives of Occupational and Environmental Health, 2022)

Correction to: Solvent Effects on Skin Penetration and Spatial Distribution of the Hydrophilic Nitroxide Spin Probe PCA Investigated by EPR - Pin Dong; Christian Teutloff; Jürgen Lademann; Alexa Patzelt; Monika Schäfer-Korting; Martina C. Meinke (Cell Biochemistry and Biophysics, 2022)

Sexual group composition and shelter geometry affect collective decision-making: the case of Periplaneta americana - S. C. Nicolis; A. Pin; M. Calvo Martín; I. Planas-Sitjà; J.-L. Deneubourg (Insectes Sociaux, 2020)

Solvent Effects on Skin Penetration and Spatial Distribution of the Hydrophilic Nitroxide Spin Probe PCA Investigated by EPR - Pin Dong; Christian Teutloff; Jürgen Lademann; Alexa Patzelt; Monika Schäfer-Korting; Martina C. Meinke (Cell Biochemistry and Biophysics, 2020)
Oxidative stress occurs in extrinsic skin aging processes and diseases when the enhanced production of free radicals exceeds the homeostatic antioxidant capacity of the skin. The spin probe, 3-(carboxy)-2,2,5,5-tetramethylpyrrolidin-1-oxyl (PCA), is frequently used to study the cutaneous radical production by electron paramagnetic resonance (EPR) spectroscopy. This approach requires delivering PCA into the skin, yet solvent effects on the skin penetration and spatial distribution of PCA have not been thoroughly investigated. Three solvents of ethanol, phosphate-buffered saline (PBS) and ethanol-PBS (1:1) were studied. For both human and porcine skin ex vivo, the amount of PCA in the stratum corneum (SC) was the lowest when using ethanol and very similar for PBS and ethanol-PBS. The highest amount of PCA in the viable skin layers was detected for ethanol-PBS, yet it only took up less than 5% of the total amount. The majority of PCA was localized in the SC, among which PCA with high mobility was predominantly distributed in the hydrophilic microenvironment of corneocytes and PCA with lower mobility was mainly in the less hydrophilic microenvironment of intercellular skin lipids. A higher ethanol concentration in the solvent could improve the distribution of PCA in the hydrophilic microenvironments of the SC. The results suggest that ethanol-PBS (1:1) is best-suited for delivering most PCA deep into the skin. This work enhances the understanding of solvent effects on the skin penetration and distribution of PCA and supports the utilization of PCA in studying cutaneous radical production.

Flavobacterium sharifuzzamanii sp. nov., Isolated from the Sediments of the East China Sea - Sanjit C. Debnath; Can Chen; Shu-Xia Liu; Ya-Nan Di; Dao-Qiong Zheng; Xin-Yang Li; Xue-Wei Xu; Jin-Zhong Xu; Pin-Mei Wang (Current Microbiology, 2019)

Elevational plant species richness patterns and their drivers across non-endemics, endemics and growth forms in the Eastern Himalaya - Kumar Manish; Maharaj K. Pandit; Yasmeen Telwala; Dinesh C. Nautiyal; Lian Pin Koh; Sudha Tiwari (Journal of Plant Research, 2017)

Groundwater flow, nutrient, and stable isotope dynamics in the parafluvial-hyporheic zone of the regulated Lower Colorado River (Texas, USA) over the course of a small flood - Alyse C. Briody; M. Bayani Cardenas; Pin Shuai; Peter S. K. Knappett; Philip C. Bennett (Hydrogeology Journal, 2016)

Subgroups of US IRAQ and Afghanistan veterans: associations with traumatic brain injury and mental health conditions - Carlos A. Jaramillo; Douglas B. Cooper; Chen-Pin Wang; David F. Tate; Blessen C. Eapen; Gerald E. York; Mary Jo Pugh (Brain Imaging and Behavior, 2015)

Variscan granitoids related to shear zones and faults: examples from the Central Sudetes (Bohemian Massif) and the Middle Odra Fault Zone - T. Oberc-Dziedzic; R. Kryza; C. Pin (International Journal of Earth Sciences, 2015)

Deciphering the geochronology of a large granitoid pluton (Karkonosze Granite, SW Poland): an assessment of U–Pb zircon SIMS and Rb–Sr whole-rock dates relative to U–Pb zircon CA-ID-TIMS - R. Kryza; C. Pin; T. Oberc-Dziedzic; Q.G. Crowley; A. Larionov (International Geology Review, 2014)

Genetic variations in TP53 binding sites are predictors of clinical outcomes in prostate cancer patients - Victor C. Lin; Chao-Yuan Huang; Yung-Chin Lee; Chia-Cheng Yu; Ta-Yuan Chang; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Archives of Toxicology, 2014)

The state and conservation of Southeast Asian biodiversity - Navjot S. Sodhi; Mary Rose C. Posa; Tien Ming Lee; David Bickford; Lian Pin Koh; Barry W. Brook (Biodiversity and Conservation, 2010)

Genetic structuring in the freshwater mussel Anodonta corresponds with major hydrologic basins in the western United States - KAREN E. MOCK; JAYNE C. BRIM BOX; JER PIN CHONG; JEANETTE K. HOWARD; DONNA A. NEZ; DAVID WOLF; RICHARD S. GARDNER (Molecular Ecology, 2010)

Three deeply divided lineages of the freshwater mussel genus Anodonta in western North America - Jer Pin Chong; Jayne C. Brim Box; Jeanette K. Howard; David Wolf; Terry L. Myers; Karen E. Mock (Conservation Genetics, 2008)

Compositions and source apportionments of atmospheric aerosol during Asian dust storm and local pollution in central Taiwan - Man-Ting Cheng; Wei-Chun Chou; Chia-Pin Chio; Shih-Chieh Hsu; Yi-Ru Su; Pei-Hsuan Kuo; Ben-Jei Tsuang; Shuen-Hsin Lin; Charles C.-K. Chou (Journal of Atmospheric Chemistry, 2008)

Early Palaeozoic crustal melting in an extensional setting: petrological and Sm–Nd evidence from the Izera granite-gneisses, Polish Sudetes - T. Oberc-Dziedzic; C. Pin; R. Kryza (International Journal of Earth Sciences, 2005)

Detection of a novel border disease virus subgroup in Tunisian sheep - F. Thabti; C. Letellier; S. Hammami; M. Ppin; M. Ribire; A. Mesplde; P. Kerkhofs; P. Russo (Archives of Virology, 2005)

The northern Ossa-Morena Cadomian batholith (Iberian Massif): magmatic arc origin and early evolution - A. Bandrs; L. Eguluz; C. Pin; J. L. Paquette; B. Ordez; B. Le Fvre; L. A. Ortega; J. I. Gil Ibarguchi (International Journal of Earth Sciences, 2004)

Mercury Distribution in Farmlands Downstream from an Acetaldehyde Producing Chemical Company in Qingzhen City, Guizhou, People?s Republic of China - Y. Yasuda; A. Matsuyama; A. Yasutake; M. Yamaguchi; R. Aramaki; L. Xiaojie; J. Pin; A. Yumin; L. Li; L. Mei; C. Wei; Q. Liya (Bulletin of Environmental Contamination and Toxicology, 2004)

The Activation Mechanism of Class-III G-Protein Coupled Receptors - J.-P. Pin; J. Kniazeff; C. Goudet; A.-S. Bessis; P. Rondard; J. Liu; F. Acher; T. Galvez; L. Przeau (Medicinal Chemistry Research, 2004)

Relics of an early-Panafrican metabasite-metarhyolite formation in the Brno Massif, Moravia, Czech Republic - F. Finger; M. Tichomirowa; C. Pin; P. Hanžl (International Journal of Earth Sciences, 2000)

Virulence factors—Pathogenicity relationships forAeromonas species from clinical and food isolates - C. Pin; P. Morales; M. L. Marín; M. D. Selgas; M. L. García; C. Casas (Folia Microbiologica, 1997)